2020
DOI: 10.1002/jmv.26386
|View full text |Cite
|
Sign up to set email alerts
|

Placental SARS‐CoV‐2 in a pregnant woman with mild COVID‐19 disease

Abstract: Background The full impact of COVID‐19 on pregnancy remains uncharacterized. Current literature suggests minimal maternal, fetal, and neonatal morbidity and mortality. 1 COVID‐19 manifestations appear similar between pregnant and non‐pregnant women. 2 Objectives/Study Design We present a case of placental SARS‐CoV‐2 virus in a woman with mild COVID‐19 disease, then review the literature. RT‐PCR was performed to detect SARS‐CoV‐… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 36 publications
3
83
0
4
Order By: Relevance
“…Another study by Blitz et al [103], reported no significant difference between the rates of ICU admission in hospitalized COVID-19 pregnant woman (9.8%; 8/82), and non-pregnant COVID-19 positive patients (15.1%; 50/3320) (p = 0.22). These studies suggest that hospitalized pregnant SARS CoV-2 positive patients are not at an increased risk for severe disease progression compared with non-pregnant COVID-19 positive hospitalized woman [102,103].…”
Section: Sexual Transmission In Womenmentioning
confidence: 78%
See 1 more Smart Citation
“…Another study by Blitz et al [103], reported no significant difference between the rates of ICU admission in hospitalized COVID-19 pregnant woman (9.8%; 8/82), and non-pregnant COVID-19 positive patients (15.1%; 50/3320) (p = 0.22). These studies suggest that hospitalized pregnant SARS CoV-2 positive patients are not at an increased risk for severe disease progression compared with non-pregnant COVID-19 positive hospitalized woman [102,103].…”
Section: Sexual Transmission In Womenmentioning
confidence: 78%
“…There was no vertical transmission detected in all 310 neonates [101]. COVID-19 symptom progression during pregnancy compared to non-pregnant women was analyzed by Hsu at al., who showed that 8.3% (36/431) of the COVID-19 patients during pregnancy had severe disease, of whom 86% (31/36) progressed to a critical stage and were admitted to the ICU [102]. Another study by Blitz et al [103], reported no significant difference between the rates of ICU admission in hospitalized COVID-19 pregnant woman (9.8%; 8/82), and non-pregnant COVID-19 positive patients (15.1%; 50/3320) (p = 0.22).…”
Section: Sexual Transmission In Womenmentioning
confidence: 99%
“…A higher frequency of maternal vascular malperfusion (MVM) of the placental bed was reported in placentas of pregnant women infected with SARS-CoV-2 by 13 studies [ 16 , 22 , 23 , 25 , 27 , 28 , 31 , 32 , 38 , 40 , 42 , 43 , 44 ]. It is a recognized pattern of placental injury related to abnormal uterine perfusion, leading to a myriad of pathological changes such as accelerated villous maturation, increased perivillous and intervillous fibrin deposition, decidual vasculopathy, Tenney–Parker change, villous infarction, and intervillous thrombosis [ 75 ].…”
Section: Placental Morphological Changesmentioning
confidence: 99%
“…Reference lists of the included papers were also checked to identify additional relevant studies. We reviewed all articles (both peer-reviewed and preprints) with reports on placental pathology in pregnant women tested positive for SARS-CoV-2 that were published between 1 January 2020 to 10 October 2020 ( n = 29) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Articles written in languages other than English and Mandarin were excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Hsu and colleagues described a case report of a pregnant woman with COVID-19 who had mild symptoms of COVID-19 prior to her delivery at 40 4 weeks gestation of a healthy infant who tested negative for the virus using RT-PCR [35]. The infant's placenta showed chronic villitis and hypertrophic arteriopathy.…”
Section: Placental Pathology From Mothers With Covid-19 In the Absencmentioning
confidence: 99%